Strategi Koping dan Pemberdayaan Disabel Netra pada Lembaga Wyata Guna di Kota Bandung - Tubagus Tamma Randi Fadilla (Umbara, 2018)
This research describes the lives and development program of visually impaired people in Bandung. This research applied the descriptive-qualitative method in particular life history model. The data were collected through observation and interview. The results of this research suggest that visually impaired people, especially caused due to accidents are depressed and helpless. They overcome depression in various ways, one of them by participating in empowerment activity. In this activity, they gain massage skills that later become their mainstays of livelihood.